2015
DOI: 10.1002/cncr.29301
|View full text |Cite
|
Sign up to set email alerts
|

Identification of geographic clustering and regions spared by cutaneous T‐cell lymphoma in Texas using 2 distinct cancer registries

Abstract: Background Cutaneous T-Cell Lymphomas (Mycosis Fungoides and its leukemic variant, Sézary Syndrome) are rare malignancies. Reports of occurrence of Mycosis Fungoides in married couples and families raise the possibility of an environmental trigger for this cancer. While it was suggested that CTLC arises from inappropriate T cell stimulation, currently no preventable trigger has been identified. Methods We analyzed by region, zip code, age, sex and ethnicity the demographic data of 1047 patients from Texas, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 29 publications
2
56
1
1
Order By: Relevance
“…Recent studies also revealed that CTCL may occur in married couples(4) and cluster in families(5). Recent investigations demonstrated geographic clustering of CTCL cases, therefore implying possible existence of an environmental trigger for this malignancy (6) though this remains to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also revealed that CTCL may occur in married couples(4) and cluster in families(5). Recent investigations demonstrated geographic clustering of CTCL cases, therefore implying possible existence of an environmental trigger for this malignancy (6) though this remains to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Clues pointing to attribution of environmental exposure include the concomitant rise in CTCL cases with industrial expansion, increased incidence in nonblood‐related relatives, and known associations of occupational chemicals with other hematologic malignancies . Clustering has been identified in several studies across the globe, including Sweden, Canada, Pittsburgh, Pennsylvania, and Texas . The analysis in Texas found 3 communities in metropolitan Houston with rates of CTCL that were between 5 and 20 times higher than the expected population rate .…”
Section: Introductionmentioning
confidence: 99%
“…Clustering has been identified in several studies across the globe, including Sweden, Canada, Pittsburgh, Pennsylvania, and Texas . The analysis in Texas found 3 communities in metropolitan Houston with rates of CTCL that were between 5 and 20 times higher than the expected population rate . Each of these studies of geographic clustering of CTCL had proposed environmental and occupational exposures as inciting factors, but further analysis of toxic exposures had not previously been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Demographic patterns in the incidence of CTCL have been reported, but no environmental triggers have yet been identified [16, 17]. Likewise, no convincing evidence showing an etiologic role of infectious agents in CTCL has been provided, albeit infections may aggravate the disease [18].…”
Section: Introductionmentioning
confidence: 99%